2020
DOI: 10.3904/kjim.2020.180
|View full text |Cite|
|
Sign up to set email alerts
|

Lung ultrasound for early diagnosis and severity assessment of pneumonia in patients with coronavirus disease 2019

Abstract: Background/Aims: Current evidence supports lung ultrasound as a point-ofcare alternative diagnostic tool for various respiratory diseases. We sought to determine the utility of lung ultrasound for early detection of pneumonia and for assessment of respiratory failure among patients with coronavirus disease 2019 (COVID-19). Methods: Six patients with confirmed COVID-19 by reverse transcription-polymerase chain reaction were enrolled. All had undergone chest X-ray and chest computed tomography (CT) on the day of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 23 publications
0
24
0
5
Order By: Relevance
“…LUS is a fast, accurate, and portable examination that can be performed in real time with no radiation exposure, to evaluate lung lesions. However, only a few studies have reported employing LUS to assess COVID-19 pneumonia severity [28] , [29] , [30] , and these were mainly descriptive studies or narrative reviews. A study found that LUS was performed to assess the severity of respiratory failure in six patients with COVID-19 [28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LUS is a fast, accurate, and portable examination that can be performed in real time with no radiation exposure, to evaluate lung lesions. However, only a few studies have reported employing LUS to assess COVID-19 pneumonia severity [28] , [29] , [30] , and these were mainly descriptive studies or narrative reviews. A study found that LUS was performed to assess the severity of respiratory failure in six patients with COVID-19 [28] .…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have reported employing LUS to assess COVID-19 pneumonia severity [28] , [29] , [30] , and these were mainly descriptive studies or narrative reviews. A study found that LUS was performed to assess the severity of respiratory failure in six patients with COVID-19 [28] . Another study that recruited ten patients with COVID-19 suggested that LUS score monitoring seemed to reflect disease progression [29] .…”
Section: Discussionmentioning
confidence: 99%
“… Huang et al 18 Ssytematic review and meta-analysis Thoracic CT presents high sensitivity and low specificity in the detection of COVID-19, and should be performed in individuals with certain clinical characteristics, together with RT-PCR. Cho et al 19 Retrospective review (n=6) LUS has proven to be a fast and sensitive method as a screening tool to detect pneumonia and assess the severity of respiratory failure in hospitalized patients with COVID-19. Smargiassi et al 20 Review In pediatric patients admitted in the emergency room with symptoms similar to COVID-19, LUS should be performed early.…”
Section: Resultsmentioning
confidence: 99%
“…Imaging examinations are essential for diagnosis and for the early detection and monitoring of COVID-19. 5 , 17 CT is a widely used instrument in the investigation of the infection, 5 , 17 , 18 , 19 even though it does not distinguish it from other viral pneumonias. 17 However, CT exposes patients to unnecessary radiation, and health professionals, to higher risk of cross contamination in the hospital.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation